Risk of venous thromboembolism in children after general surgery - Humes, David J.; Nordenskjöld, Agneta; Walker, Alex J.; West, Joe; Ludvigsson, Jonas F. (Elsevier, 2015)
Background/purpose: The purpose of the study was to determine absolute and relative rates of venous thromboembolism (VTE) following general surgical procedures in children compared to the general population.